A SIMPLE RAPID PROCEDURE FOR HEMOGLOBIN ELECTROPHORESIS USING A DROP OF DRIED BLOOD ON FILTER PAPER - S. Rahbar; H. Heidary; I. Mostafavi (Tehran University of Medical Sciences, 1974)
A simple, rapid new technique is described for the electrophoresis of hemoglobin when screening large human populations. The method uses a drop of finger tip's blood dried on a thick filter paper as the specimen. The simplicity of the sampling, tagging, transportation and electrophoresis, provides a reliable procedure for surveys of large population. In our hand 200 specimens were screened during a working day by two technicians with a very good resolution of hemoglobin band. Even small amount of fetal hemoglobin could be separated from normal adult hemoglobin by this technique. During last 8 months, 20,000 individua1s were screened by this technique and a number of known and unknown hemoglobin variants were detected which are reported elsewhere.